Tethered 3-min all-out test did not predict the traditional critical force parameters in inexperienced swimmers - Kalva-Filho, Carlos A.; Zagatto, Alessandro M. [UNESP]; Da Silva, Adelino S.; Castanho De Araújo, Monique Y. [UNESP]; De Almeida, Pablo B.; Papoti, Marcelo (Edizioni Minerva Medica, 2017)
Background: Critical power model can be performed in tethered swimming (i.e. critical force model). Although critical force can be used to prescribe aerobic training, its determination depends on at least three exhaustive efforts in altered days. In this context, previously studies have demonstrate that critical power model can be estimated by a single 3-min all-out test (3MT), which was not investigated in swimming yet. Thus, the aim of this study was to compare the parameters obtained during the tethered swimming 3MT to those obtained during the traditional critical force model. Methods: Seven swimmers (four female and three male) underwent a tethered swimming 3MT and three exhaustive efforts to determine the traditional critical force parameters (i.e. critical force [CF] and anaerobic impulse capacity [AIC]). Results: The critical force (CF3-MIN) and force-time integral above the CF3-MIN (AIC3-MIN) determined during the tethered 3MT were not different to CF and AIC, respectively (P value >0.55). However, these parameters were not correlated (P value >0.45). In addition, we verified large limits of agreement between CF3MIN and CF (±19.7 N), which was also observed between AIC3MIN and AIC (±0.84 Log[N·min]). Conclusions: These findings demonstrated that tethered 3MTs should not be used to predict traditional critical force parameters, at least when the swimmers are inexperienced in long tethered all-out efforts.
Keywords: Exercise test; Sports; Swimming